Life paths and environmentalism in South America. A cross-link between the individual and the collective - Barzola, Erika Judith (2017)
During 2013 and 2015 we carried out a research work, in the city of Córdoba, Argentina, which allowed us to identify three   environmentalism currents that keep an interesting counterpoint with the currents advocated by Martinez Alier: the environmental protection, the socio-environmental rights and the life environment. In addition, we were able to trace different life paths from diverse socio-environments activists, which allowed us understand how these life paths are combined and contribute to characterize and itemize environmentalism. Throughout this paper we want to present the different life paths which we were able to identify with our research and then, to explain the intersections given between life paths and the traces and characteristic of the identified environmentalism.